Countdown : a novel - Wiles, Deborah (Wiles, Deborah. Sixties trilogy, 2013)
Set in the fear-laden sixties when duck-and-cover drills sent kids cowering under their desks, this novel follows Franny as she tries to make sense of the pervading threat of nuclear devastation, sibling tension, and her place in this complex world. Contains photos, news clips, and songs from the time.